A correlation between performance and graphic presentation in unit trust's annual report - Saad, Ram Al Jaffri; Yahya, Mohd Azlan; Md Hussain, Md Hairi (2006)
This paper investigates the extent use of graphs, the types of graphs and the types of information being presented graphically in unit trust’s annual reports. The paper formulates and test hypothesis concerning selectivity in the use of graphs. Results show that 78 per cent of unit trust’s annual reports use graphs and that 2.1 is the mean number of graphs per graph-using companies. The most commonly graphed financial variables are asset allocation, performance, investment and fund size. Line and pie graphs are more popular than bar and column. Thus, contrast to studies of graphs in annual report, no correlation is found between performance and graphic presentation in unit trust’s annual report. This is because the graphic presentation in unit trust’s annual report is normally dependent on discretion of company’s management.